PENINGKATAN KINERJA GURU DENGAN MENGEFEKTIFITASKAN KEPEMIPINAN KEPALA SEKOLAH DI MAS YPI BATANG KUIS - Ahmad Mukhlasin (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The purpose of this paper is to see the effectiveness of the principal's leadership in improving teacher performance at MAS YPI Batang Kuis. This research was conducted at MAS YPI Batang Kuis. The research was conducted on December 22, 2021. The subject of this research is the school owner who acts as a leader at MAS YPI Batang Kuis. The data collection technique is by interview. The results of this study are: (1). The leadership behavior at MAS YPI Batang Quiz in teacher performance management is to always provide direction to teacher activities and student activities at school, provide motivation to teachers in carrying out learning at school, always communicate well with all teachers at school, be disciplined and firm in every decision making at school, and Creating a family relationship at school both to teachers, students and other staff. (2). The influence on teacher performance in schools can be seen from four aspects, namely discipline aspects, religious aspects, cooperation aspects, leadership aspects. (3). The forms of the principal's performance management strategy in improving teacher performance are 1) a strategy for providing allowances/salaries/rewards, 2) paying attention to teachers, 3) providing teacher-coaches in honing teacher skills, 4) empowering teachers in decision making.Leadership Effectiveness, Teacher Performance